COMPARISON OF QUICKSORT AND MERGESORT METHOD FOR USER INTERFACE AND USER EXPERIENCE ASSESSMENT IN ADISUTJIPTO COLLEGE OF TECHNOLOGY - Abidin, Muhammad Zainal; Nugraheny, Dwi; Indrianingsih, Yuliani (Compiler, 2020)
This study is intended to assess the user interface and user experience on the Adisutjipto College of Technology website using the mergesort method and compared with the quicksort method in finding the highest value of several variables or elements that are categorized as good or good in order to improve the quality of the Adisutjipto College of Technology website. The results of the study show that the quicksort method is faster in the process of calculating questionnaire data than the merge method with an average time record of 0.476667 seconds for the quicksort method and 0.576667 seconds for the mergesort method. The results of the comparison of the two methods on the questionnaire website to assess the accuracy in terms of user interface and user experience on the Adisutjipto College of Technology website, that the mergesort method is more accurate than the quicksort method, the Usability category scores the highest, while the Expressive aesthentics category has the lowest value